Discursive approaches to politeness (Mouton series in pragmatics ;, 2011)
This collection of essays by the Linguistic Politeness Research Group represents the results of over a decade of the group's research, discussions, seminars and conferences on the subject of linguistic politeness. The volume brings together cutting edge essays reflecting the range of discursive approaches to the analysis of politeness and impoliteness.